Applied fluid mechanics - Mott, Robert L. (Merrill, 1994)
The most popular applications-oriented approach to engineering technology fluid mechanics, this text covers all of the basic principles of fluid mechanics-both statics and dynamics-in a clear, practical presentation that ties theory directly to real devices and systems used in chemical process industries, manufacturing, plant engineering, waste water handling and product design. Readable and clearly written, the new 6th edition brings a much more attractive appearance to the book and includes many updates and additional features.